Pengaruh Nilai Hedonik dan Utilitarian terhadap Kepuasan Berbelanja Melalui Aplikasi Shopee pada Mahasiswa STIE Widya Praja Tanah Grogot - Karlina Karlina; Tegen Sayuk Rimboko (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the influence of hedonic value and utilitarian value on students' shopping satisfaction through the Shopee application. The research population consisted of active Shopee users among students of STIE Widya Praja Tanah Grogot, with a sample of 100 respondents selected using purposive sampling technique. A quantitative research method with a survey approach using structured questionnaires was employed. Data were analyzed using multiple linear regression with SPSS version 26. The results indicate that hedonic value has a positive and significant effect on shopping satisfaction (β = 0.412; p < 0.05), utilitarian value has a positive and significant effect on shopping satisfaction (β = 0.358; p < 0.05), and simultaneously both values significantly influence shopping satisfaction with a coefficient of determination (R²) of 0.624. These findings imply that e-commerce platforms such as Shopee need to strengthen enjoyable shopping experiences while providing tangible functional benefits for consumers.